Preparation method and application of alkali metal doped modified aqueous zinc ion vanadium-based positive electrode material
By doping alkali metal and conductive carbon materials into the vanadium-based positive electrode material of the aqueous zinc ion battery and using hydrothermal treatment, the problems of unstable material structure and poor conductivity are solved, and the effects of high capacity, good cycle stability and improved rate performance are achieved.
Patent Information
- Application Number
- CN202411704330.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-18
AI Technical Summary
The vanadium-based positive electrode materials of existing water-based zinc-ion batteries have problems such as low voltage window, easy dissolution during circulation, and structural collapse. In particular, the short layer spacing of V2O5 materials is not conducive to ion diffusion and poor conductivity.
By doping alkali metal salts and conductive carbon materials in V2O5, the reaction is carried out by hydrothermal method, the lattice layer spacing and electronic characteristics of V2O5 are adjusted, the material structure is stabilized and the conductive properties are improved.
The specific capacity and cyclic stability of vanadium-based positive electrode materials are significantly improved, and the rate performance and overall electrochemical performance are improved.
Smart Images

Figure CN119650622A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of aqueous zinc ion battery materials, and in particular relates to a preparation method and application of an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material. Background Art
[0002] In recent years, with the rapid development of economy and the rapid progress of society, people's demand for energy is getting higher and higher. Traditional fossil energy is gradually being replaced by green new energy due to a series of environmental problems such as greenhouse effect caused by combustion. At present, lithium-ion batteries are favored because of their advantages such as high voltage window, high energy density and long cycle life. However, lithium-ion batteries also have a series of problems, such as lack of lithium resources, flammable organic electrolytes, and high costs, which hinder their further development and application in the future. Therefore, it is necessary to find a new type of battery that can replace lithium-ion batteries.
[0003] The zinc metal anode of aqueous zinc-ion batteries has a low redox potential (-0.76 V vs. standard hydrogen electrode (SHE)), a high theoretical specific capacity (820 mAh g -1 and 5855mAh cm -3 ), low price, abundant storage, and environmental friendliness have attracted much attention. At present, the positive electrode materials of aqueous zinc-ion batteries mainly include manganese-based compounds, vanadium-based compounds, and Prussian blue analogs. Among them, manganese-based positive electrode materials have poor rate performance and cycle performance; Prussian blue analogs have poor capacity, even less than 100mAh g -1 . Vanadium-based cathode materials have high theoretical specific capacity and excellent rate characteristics, and have broad prospects in aqueous zinc-ion batteries. Unfortunately, vanadium-based cathode materials have problems such as low voltage window, easy dissolution during cycling, and structural collapse; among them, V2O5 materials also have short interlayer spacing that is not conducive to the diffusion of ions, and the V2O5 cathode has poor conductivity. Therefore, it is very important to find a way to stabilize the crystal structure of the material. Summary of the invention
[0004] In view of the above problems existing in the background technology, the present invention provides a preparation method and application of an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material. The prepared positive electrode material has the advantages of stable crystal structure and strong cycle stability.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material, the method comprising:
[0007] S1: Fully dissolve V2O5 in deionized water to form a light yellow liquid; then add alkali metal salt and stir thoroughly to obtain a mixed solution A;
[0008] S2: adding the conductive carbon material into deionized water and ultrasonically treating the water to obtain solution B;
[0009] S3: adding solution B to mixed solution A, stirring thoroughly and performing a hydrothermal reaction;
[0010] S4: After the reaction kettle is cooled to room temperature, it is washed by centrifugation and then freeze-dried in a freeze dryer to obtain an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material, which is placed in a blast dryer for drying before use. The vanadium-based positive electrode material has a uniform nanostructure. The present invention obtains a suitable positive electrode material by selecting different alkali metal salts, conductive carbon materials, and hydrothermal reaction time and temperature.
[0011] Furthermore, in step S1, the alkali metal salt is a fluoride salt. The alkali metal includes one or more of lithium, sodium, potassium, rubidium, cesium, and francium.
[0012] Furthermore, in step S1, in the mixed solution A, the molar ratio of the alkali metal salt to V2O5 is 1 to 4:1.
[0013] Furthermore, in step S2, in the solution B, the concentration of the conductive carbon material is 1.0-2.0 g / L, and the ultrasonic time is controlled at 0.5-1.5 h; the conductive carbon material includes graphene oxide (GO) and / or carbon nanotubes (CNT).
[0014] Furthermore, in step S3, the temperature of the hydrothermal reaction is 120-200° C., and the time is 6-24 hours.
[0015] Furthermore, in step S4, the centrifugal washing solution is deionized water, the centrifugal frequency is 8000 rpm / min, the centrifugal time is 10 minutes, the number of centrifugal washings is 3 times, the solution before each centrifugation is subjected to ultrasonic treatment, and the freeze-drying time is 24 to 48 hours.
[0016] An alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material prepared by the above preparation method is used as a positive electrode material in an aqueous zinc ion battery.
[0017] The beneficial effects of the present invention compared to the prior art are:
[0018] 1. The present invention adopts a hydrothermal method for preparation, which has a simple preparation method, mild conditions and wide applicability.
[0019] 2. By doping with alkali metals, the lattice interlayer spacing and electronic properties of V2O5 can be effectively adjusted, which can significantly improve the specific capacity and cycle stability; the introduced carbon materials can also improve the conductivity of the material and improve the rate performance of the battery.
[0020] The present invention uses alkali metal doping to widen the interlayer spacing of V2O5, improve the embedding / extraction of zinc ions in V2O5, and act as a "pillar" to stabilize the structure of the material; in addition, conductive carbon materials are introduced to improve the conductivity of the positive electrode material. The modified vanadium-based positive electrode exhibits high capacity, significantly improved rate performance, and greatly enhanced cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The figure is a rate performance diagram of the battery assembled with the positive electrodes described in Examples 1 to 3 of the present invention and Comparative Example 1 at different current densities;
[0022] Figure 2 The battery assembled with the positive electrodes described in Examples 1 to 3 of the present invention and Comparative Example 1 was subjected to a current density of 0.1 A g -1 Cycle performance diagram below;
[0023] Figure 3 The battery assembled with the positive electrodes described in Examples 1 to 3 of the present invention and Comparative Example 1 was subjected to a current density of 5Ag. -1 The cycle performance diagram below. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with specific embodiments. It should be noted that all the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0025] Example 1
[0026] A method for preparing an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material comprises the following steps:
[0027] S1. Take a clean beaker, add 5mmol V2O5 powder, then add 40ml deionized water, stir thoroughly to dissolve, form a light yellow solution, then add 15mmol LiF powder, stir thoroughly to obtain a mixed solution A;
[0028] S2. Take a clean beaker, add 20 ml of deionized water, weigh 10 mg of graphene oxide, add it to the deionized water and stir thoroughly for 30 minutes, then ultrasonically treat for 1 hour to obtain solution B.
[0029] S3. Add solution B in S2 to mixed solution A in S1 under stirring conditions. After fully mixing, take a clean 100 ml polytetrafluoroethylene liner, add the obtained mixed solution to the polytetrafluoroethylene liner, and place the above liner in a reactor to react at 180°C for 8 hours.
[0030] S4. After the reaction is completed, the reactor is cooled to room temperature and the obtained product is taken out. The obtained product is placed in a centrifuge and centrifuged with deionized water for washing. The centrifugal frequency is 8000 rpm / min, the centrifugal time is 10 min, the number of centrifugations is 3, and the product is evenly dispersed by ultrasonication for 10 min before each centrifugation. The product after centrifugal washing is freeze-dried for 24 h to obtain the Li-V2O5@GO zinc ion battery positive electrode material, which is placed in a 60°C forced air drying oven for use.
[0031] Example 2
[0032] A method for preparing an alkali metal-doped modified aqueous zinc ion battery vanadium-based positive electrode comprises the following steps:
[0033] S1. Take a clean beaker, add 5mmol V2O5 powder, then add 40ml deionized water, stir thoroughly to dissolve, form a light yellow solution, then add 10mmol NaF powder, stir thoroughly to obtain a mixed solution A;
[0034] S2. Take a clean beaker, add 20 ml of deionized water, weigh 10 mg of graphene oxide, add it to the deionized water and stir thoroughly for 30 minutes, then ultrasonically treat for 1 hour to obtain solution B.
[0035] S3. Add solution B in S2 to mixed solution A in S1 under stirring conditions. After fully mixing, take a clean 100 ml polytetrafluoroethylene liner, add the obtained mixed solution to the polytetrafluoroethylene liner, and place the above liner in a reactor to react at 200°C for 8 hours.
[0036] S4. After the reaction is completed, the reactor is cooled to room temperature and the obtained product is taken out. The obtained product is placed in a centrifuge and centrifuged with deionized water for washing. The centrifugal frequency is 8000 rpm / min, the centrifugal time is 10 min, the number of centrifugations is 3, and the product is evenly dispersed by ultrasonication for 10 min before each centrifugation. The product after centrifugal washing is freeze-dried for 24 h to obtain Na-V2O5@GO zinc ion battery positive electrode material, which is placed in a 60°C forced air drying oven for use.
[0037] Example 3
[0038] A method for preparing an alkali metal-doped modified aqueous zinc ion battery vanadium-based positive electrode comprises the following steps:
[0039] S1. Take a clean beaker, add 5mmol V2O5 powder, then add 40ml deionized water, stir thoroughly to dissolve, form a light yellow solution, then add 10mmol KF powder, stir thoroughly to obtain a mixed solution A;
[0040] S2. Take a clean beaker, add 20 ml of deionized water, weigh 10 mg of carbon nanotubes, add to the deionized water and stir thoroughly for 30 min, then ultrasonically treat for 1 h to obtain solution B.
[0041] S3. Add solution B in S2 to mixed solution A in S1 under stirring conditions. After fully mixing, take a clean 100 ml polytetrafluoroethylene liner, add the obtained mixed solution to the polytetrafluoroethylene liner, and place the above liner in a reactor to react at 200°C for 10 hours.
[0042] S4. After the reaction is completed, the reactor is cooled to room temperature and the obtained product is taken out. The obtained product is placed in a centrifuge and centrifuged with deionized water for washing. The centrifugal frequency is 8000 rpm / min, the centrifugal time is 10 min, the number of centrifugations is 3, and the product is evenly dispersed by ultrasonication for 10 min before each centrifugation. The product after centrifugal washing is freeze-dried for 24 h to obtain K-V2O5@GO zinc ion battery positive electrode material, which is placed in a 60°C forced air drying oven for use.
[0043] Comparative Example 1
[0044] A method for preparing an alkali metal-doped modified aqueous zinc ion battery vanadium-based positive electrode comprises the following steps:
[0045] S1. Take a clean beaker, add 5mmol V2O5 powder, then add 40ml deionized water, stir thoroughly to dissolve, and form a light yellow solution to obtain solution A;
[0046] S2. Take a clean beaker, add 20 ml of deionized water, weigh 10 mg of graphene oxide, add it to the deionized water and stir thoroughly for 30 minutes, then ultrasonically treat for 1 hour to obtain solution B.
[0047] S3. Add solution B in S2 to solution A in S1 under stirring conditions. After fully mixing, take a clean 100 ml polytetrafluoroethylene liner, add the resulting mixed solution to the polytetrafluoroethylene liner, and place the liner in a reactor to react at 200°C for 8 hours.
[0048] S4. After the reaction is completed, the reactor is cooled to room temperature and the obtained product is taken out. The obtained product is placed in a centrifuge and centrifuged with deionized water for washing. The centrifugal frequency is 8000 rpm / min, the centrifugal time is 10 min, the number of centrifugations is 3, and the product is evenly dispersed by ultrasonication for 10 min before each centrifugation. The product after centrifugal washing is freeze-dried for 24 h to obtain an unmodified V2O5@GO zinc ion battery positive electrode material, which is placed in a 60°C forced air drying oven for use.
[0049] The positive electrode materials obtained in Examples 1-3 and Comparative Example 1 are respectively applied to aqueous zinc ion batteries and include the following steps:
[0050] Preparation of positive electrode
[0051] The positive electrode materials, conductive agent (Super P) and PVDF obtained in the above Examples 1-3 and Comparative Example 1 were mixed in a ratio of 7:2:1, dissolved in NMP to obtain an active material slurry, and finally coated on carbon paper and cut into positive electrode discs with a diameter of 14 mm and a loading of about 1.2 mg cm -2 .
[0052] Preparation of negative electrode
[0053] A zinc foil with a thickness of 0.1 mm was cut into discs with a diameter of 16 mm, and its surface was polished with aluminum oxide. The residual contaminants on the surface were removed by ultrasonic cleaning with ethanol and then dried to obtain a negative electrode.
[0054] Preparation of electrolyte
[0055] Zinc trifluoromethanesulfonate is dissolved in deionized water to obtain an electrolyte, and the solubility of the electrolyte is 3 mol / L.
[0056] Preparation of batteries
[0057] The positive electrode sheet, the diaphragm, the negative electrode sheet, the gasket and the spring sheet are placed in the battery case in order, an electrolyte is added, and finally the battery is packaged to obtain an aqueous zinc ion battery. The diaphragm is a glass fiber diaphragm.
[0058] The electrochemical performance of aqueous zinc ion batteries assembled with the lithium, sodium, potassium ion-doped and undoped aqueous zinc ion battery vanadium-based positive electrodes obtained in Example 1, Example 2, Example 3 and Comparative Example 1 was tested. The results are shown in the figure. Figures 1 to 3 As shown. Among them, Figure 1 The figure is a rate performance diagram of the battery assembled with the positive electrodes described in Examples 1 to 3 and Comparative Example 1 at different current densities; it can be seen from the figure that compared with the vanadium-based positive electrode that has not been doped and modified in Comparative Example 1, the specific capacity and rate performance of the vanadium-based positive electrode doped and modified with lithium, sodium and potassium ions obtained in Examples 1 to 3 are significantly improved. Figure 2 The battery assembled with the positive electrodes described in Examples 1 to 3 and Comparative Example 1 was charged at a current density of 0.1 A g -1 The cycle performance diagram under the condition of Fig. 1 shows that the first cycle discharge specific capacities of Comparative Example 1 and Examples 1 to 3 are 364.95, 345.38, 304.62, and 146.29 mAh g, respectively. -1 The capacity retention rates after 200 cycles were 90.18, 76.82, 64.53, and 105.95%, respectively. Figure 3The battery assembled with the positive electrodes described in Examples 1 to 3 and Comparative Example 1 was charged at a current density of 5Ag -1 The cycle performance diagram under the current density is shown in Figure 1, where the capacity retention rates of Comparative Example 1 and Examples 1 to 3 after 2000 cycles at the current density are 96.35%, 93.53%, 89.79%, and 82.66%, respectively. It can be concluded that by doping with alkali metal ions, it acts as an interlayer pillar in V2O5, broadens the interlayer spacing of V2O5 crystals, stabilizes the crystal structure of vanadium-based positive electrode materials, increases specific capacity, improves cycle stability and rate performance, and thus improves the overall electrochemical performance of vanadium-based positive electrode materials.
[0059] The above description of the disclosed embodiments enables professionals in the field to implement or use the present invention. The above embodiments are only used to illustrate the technical solutions of the present invention and are not limiting. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention can be modified without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material, characterized in that: The method is: S1: Fully dissolve V2O5 in deionized water to form a light yellow liquid; then add alkali metal salt and stir thoroughly to obtain a mixed solution A; S2: adding the conductive carbon material into deionized water and ultrasonically treating the water to obtain solution B; S3: adding solution B to mixed solution A, stirring thoroughly and performing a hydrothermal reaction; S4: After the reactor is cooled to room temperature, centrifugal washing and freeze drying are performed to obtain an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material.
2. The method for preparing an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material according to claim 1, characterized in that: In step S1, the alkali metal salt is a fluoride salt.
3. The method for preparing an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material according to claim 1, characterized in that: In step S1, in the mixed solution A, the molar ratio of the alkali metal salt to V2O5 is 1 to 4:
1.
4. The method for preparing an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material according to claim 1, characterized in that: In step S2, in the solution B, the concentration of the conductive carbon material is 1.0-2.0 g / L, and the ultrasonic time is controlled at 0.5-1.5 h; the conductive carbon material includes graphene oxide (GO) and / or carbon nanotubes (CNT).
5. The method for preparing an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material according to claim 1, characterized in that: In step S3, the temperature of the hydrothermal reaction is 120-200° C., and the time is 6-24 hours.
6. The method for preparing an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material according to claim 1, characterized in that: In step S4, the centrifugal washing solution is deionized water, the centrifugal frequency is 8000 rpm / min, the centrifugal time is 10 minutes, the number of centrifugal washings is 3 times, the solution before each centrifugation is subjected to ultrasonic treatment, and the freeze-drying time is 24 to 48 hours.
7. Use of an alkali metal-doped modified aqueous zinc ion vanadium-based positive electrode material prepared by the preparation method according to any one of claims 1 to 6 as a positive electrode material in an aqueous zinc ion battery.